Comparative miRNome analysis of colostrum- and mature milk–derived extracellular vesicles from Holstein and Jersey cows - Daye Mun; Sangdon Ryu; Dong-Hyun Lim; Sangnam Oh; Younghoon Kim (Journal of Animal Science and Technology)
MicroRNAs (miRNAs) are small noncoding RNAs that play a pivotal role in the regulation of gene expression. Analysis of miRNAs is important for understanding a variety of biological processes. Sequencing of miRNAs within milk-derived extracellular vesicles (EVs) provides valuable insights into the molecular mechanisms through which these EVs influence recipient cells. Comparative miRNA sequencing of colostrum and mature milk from different cow breeds can demonstrate breed-specific differences and improve the understanding of potential therapeutic applications in immune regulation and gut health. Therefore, this study was conducted to compare the miRNA profiles and characteristics of colostrum- and mature milk–derived EVs from Holstein and Jersey breeds and determine their effects on intestinal epithelial cells. The miRNA profiles of EVs isolated from the colostrum and mature milk of Holstein and Jersey cows were analyzed via small RNA sequencing. Holstein colostrum–derived EVs exhibited the most diverse miRNA profile with 421 identified miRNAs compared with 259 in mature milk–derived EVs. Jersey colostrum EVs had 198 miRNAs, whereas mature milk EVs had 282. Differential expression analysis revealed considerable miRNA differences between colostrum and mature milk, particularly in Holstein cows. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses revealed that miRNAs from colostrum EVs predominantly regulated immune-related pathways. Transcriptomic analysis of human colon cell line HT-29 treated with Holstein colostrum EVs confirmed the modulation of genes associated with immune responses. These findings indicate that colostrum-derived EVs, particularly from Holstein cows, play a pivotal role in immune regulation and could be potential candidates for therapeutic applications.